(untitled) (Global Journal of Medical Research, 2023)
Background It exist increasing studies on the inflammatory process in psychiatric disorders in which inflammation in schizophrenia SZ isquestioned Objective assess the association between social anxiety SA and inflammation in patients with SZ measuring primarily the neutrophil-to-lymphocyte ratio NLR and secondarily the systemic immune-inflammation index SII monocyte-to-lymphocyte ratio MLR and platelet-lymphocyte ratio PLR Methods A cross-sectional study Results Of the 82 patients who met the inclusion criteria 59 patients had SA and observed a significant alteration in inflammation markers in patients with SZ especially NLR